Analisis Kinerja Produksi Struktur Biaya dan Pendapatan Agroindustri Keripik Tempe (Studi Kasus Agroindustri Keripik Tempe Siger Mas di Kota Metro - Fina Zahrotul Atiyah Fina; Dwi Haryono; Erlina Rufaidah (Journal of Food System & Agribusiness, 2021)
This study aims to analyze the manufacturing performance, cost structure and revenue of Siger Mas Tempe Chips Agribusiness in Metro City. This study is a case study of Tempe Siger Mas Chips' agribusiness. The respondents to this survey are founders and employees in agriculture. The study data were analyzed using quantitative and qualitative descriptive analysis (production performance analysis) and quantitative descriptive analysis (cost and revenue structure analysis). The results showed that the overall performance of the Siger Mas Tempe Chips Agroindustry was not in a good category. The largest cost component of Tempe Chips cost structure is the cost of cooking oil (25.12%), labor cost (23.09%), raw material cost (10.84%), plastic packaging cost (9.36%) and liquefied petroleum gas cost (8.13) ±  Flour Cost (6.90%), Marketing Cost (4.93%), Garlic Cost (3.20%), Aci Flour Cost (2.46%), Electricity Cost (2.46%), Depreciation Cost (1.47% ), aroma costs (1.23%) , transport costs (0.74%) and yeast costs (0.06%). Agro-industry Siger Mas Tempe Chips made a profit of Rp 8,380,487.50. It can be concluded that the agro-industry Siger Mas Tempe Chips is feasible and profitable to develop.